Analysis of Tourism Development Strategies on Banda Island (Mix Methods Approach) - Novita Suara; Djufri Pattilouw; Maryam Sangadji (Univiversitas Dr. Djar Wattiheluw, 2025)
This study aims to identify tourist attractions on Banda Island and analyze their strengths, weaknesses, opportunities, and threats to formulate appropriate development strategies. Employing a qualitative research approach, the findings reveal three main categories of tourism on Banda Island: historical tourism, cultural tourism, and marine tourism. Among these, historical and marine tourism are the most frequently visited, comprising six and seven tourist sites, respectively, making them significant attractions within Maluku Province. The analysis identifies four strengths, five weaknesses, three opportunities, and four threats influencing the development of Banda Island’s tourism sector. Moreover, the government plays a pivotal role in fostering tourism development on the island. Based on the findings, an aggressive, growth-oriented strategy is recommended as the most suitable approach for advancing Banda Island’s tourism industry.